Hubungan Pola Asuh Otoriter dengan Kemampuan Kreativitas Anak Usia 4-5 Tahun di TPA Al-Fajril Ulum - Salsa Aprilla Patilima; Nurul Aini Mm. Sodik; Tria Oktaviani Jannati; Anisa Safwa Ilato; Farah Angraini (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to analyze the relationship between authoritarian parenting and early childhood creativity. Creativity is an important aspect of child development because it plays a role in shaping the ability to think, solve problems, and express ideas freely. However, the process of creativity development is often influenced by parenting styles at home. Authoritarian parenting is known as a parenting style that tends to be rigid, full of control, and demands obedience without providing space for children to express their opinions. This study used a quantitative approach with a correlational design involving children aged 4–6 years and their parents. Data were obtained through parenting questionnaires and observations of children's creativity. The results showed a negative relationship between authoritarian parenting and creativity. The higher the level of authoritarianism applied, the lower the child's creativity. This finding emphasizes the importance of more open parenting for optimal development of children's creativity.